Mustafa Barzani's roleIn forming and leading political organizations and institutions) 1945-1975) - Saadi Othman Harruti; Qaraman Haidar Rahman (Zanco Journal of Humanity Sciences)
The emergence of Mustafa Barzani as the leader of the Kurdish liberation movement between 1945 and 1975 is considered a turning point in the history of the Kurdish national movement. On this basis, Dennis Chapman, the chief US military adviser, described the leader as the father of the Kurdish liberation movement. Because the Kurdish liberation movement during the Barzani era was one of its political elements, the formation and leadership of political organizations and institutions in southern Kurdistan, such as the formation of the Freedom Committee in 1945 and the establishment of the Kurdistan Democratic Party in August. Provisional government in Baku, the capital of Soviet Azerbaijan, in December 1948 and the establishment of the Revolutionary Command Council of Iraqi Kurdistan in 1964. In April 1974, in consultation with the leadership of the pdk, it decided to form a Council of General Secretariats to manage the affairs of the liberated areas under the control of the Kurdistan Peshmerga forces. The institution continued to provide services to the Kurdish people until the end of the revolution.